Investments - Bodie, Zvi; Kane, Alex, 1942-; Marcus, Alan J. (New York, NY : McGraw-Hill Education, 2018)
"The integrated solutions for Bodie, Kane, and Marcus' Investments set the standard for graduate/MBA investments textbooks. The unifying theme is that security markets are nearly efficient, meaning that most securities are priced appropriately given their risk and return attributes. The content places greater emphasis on asset allocation and offers a much broader and deeper treatment of futures, options, and other derivative security markets than most investment texts. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective." --
Preface -- Part I: Introduction. The investment environment ; Asset classes and financial instruments ; How securities are traded ; Mutual funds and other investment companies -- Part II: Portfolio theory and practice. Risk, return, and the historical record ; Capital allocation to risky assets ; Optimal risky portfolios ; Index models -- Part III: Equilibrium in capital markets. The capital asset pricing model ; Arbitrage pricing theory and multifactor models of risk and return ; The efficient market hypothesis ; Behavioral finance and technical analysis ; Empirical evidence on security returns -- Part IV: Fixed-income securities. Bond prices and yields ; The term structure of interest rates ; Managing bond portfolios -- Part V: Security analysis. Macroeconomic and industry analysis ; Equity valuation models ; Financial statement analysis -- Part VI: Options, futures, and other derivatives. Options markets : introduction ; Option valuation ; Futures markets ; Futures, swaps, and risk management -- Part VII: Applied portfolio management. Portfolio performance evaluation ; International diversification ; Hedge funds ; The theory of active portfolio management ; Investment policy and the framework of the CFA Institute -- References to CFA problems -- Glossary -- Formulas.
Includes indexes.
BBS
STS International
Keywords: Investments; Portfolio management; Business; Business & finance